GE_GERICHTE P/6901/2025 vom 24. September 2025 - GE Cour de justice (2025)
OPPOSITION TARDIVE;NOTIFICATION DE LA DÉCISION;ENVOI RECOMMANDÉ;FARDEAU DE LA PREUVE;PRÉSOMPTION | CPP.85.al2; CPP.87; CPP.354